Fabrication and characterization of a robust and strong bacterial promoter from a semi-rationally engineered promoter library in Bacillus subtilis. (October 2017) - Han, Laichuang; Suo, Feiya; Jiang, Cui; Gu, Jie; Li, Ningna; Zhang, Naixin; Cui, Wenjing; Zhou, Zhemin
Graphical abstract: Highlights: A library for promoter mutants was constructed by semi-rational design. Randomizing −10 box in bacterial promoter generates wide-range promoter activities. A robust promoter Pv1 was screened out from the mutant library. Pv1 variant has higher transcriptional activity than that of the parental promoter. Aspartase was successfully overproduced under the control of Pv1 variant. Abstract: Robust promoters have substantial usage in synthetic biology. The important biological components of these promoters, however, remain limited in Bacillus subtilis . In this study, an array of variant promoters derived from PsrfA was from a promoter library constructed by randomized mutation. By screening the library, the variant promoter Pv1 displayed the highest transcriptional activity, which was approximately 1.56-fold higher than that of native PsrfA . Moreover, Pv1 was able to trigger GFP expression at constantly increased levels over the culture period. The robustness of Pv1 was confirmed by the over-production of aspartase (aspA). B. subtilis that over-produced aspA exhibited normal cell growth and a constantly increased yield over the cultural period. Finally, aspA expression triggered by the Pv1 variant displayed a higher yield and expression levels of aspA in B. subtilis compared to those of native PsrfA . These results suggest that randomized mutation of sequences adjacent to the −10 region of the bacterial promoter significantly influenced the transcription activity of the promoter. Pv1, which has high activity and robustness, has potential applications in gene expression systems and genetic circuits in B. subtilis .